Advancement of A Modular Rotor Permanent Magnet Flux Switching Machine For High Torque Performance - Savoul Ahmid, Muhammad Rizwan; Sulaiman, Erwan (Evolution in Electrical and Electronic Engineering, 2022)
There has been recent interest in permanent magnet flux switching machines (PMFSM) that make the rotor simple, robust, and brushless with all flux sources located in the stator. However, some drawbacks of the conventional rotor and stator of PMFSM may reduce the torque and efficiency of the motor due to the flux cancellation, flux leakage and longer flux path in the motor. PMFSM based on the modular rotor is designed and investigated to ensure less use of material while high torque performance using JMAG Designer Version 14.0 software. A local optimization method is used to enhance the performance of modular rotor PMFSM. The performance of the motor has improved as the increase of torque value from an initial 56.98 to 60.28Nm, 77.49% to 82.33% of efficiency while a drop of output power from 5.17kW to 4.42kW and the objective has been achieved.